[(-1/2)la putera -2 *3 la puterea -2+0,(6)] la puterea -1 *10
Răspunsuri la întrebare
Răspuns de
1
[(-1/2)⁻² ×3⁻²+0,(6)]⁻¹ ×10 =
=[(-2)² ×1/3²+2/3)]⁻¹ ×10 =
=10/(4 ×1/9+2/3) =
=10/(4/9+2/3) =
=10/(4+6)/9 =
=9
=[(-2)² ×1/3²+2/3)]⁻¹ ×10 =
=10/(4 ×1/9+2/3) =
=10/(4/9+2/3) =
=10/(4+6)/9 =
=9
Alte întrebări interesante
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă